New insecticide delivery method for the control of Sitophilus zeamais in stored maize. (September 2019) - Peschiutta, M.L.; Brito, V.D.; Achimón, F.; Zunino, M.P.; Usseglio, V.L.; Zygadlo, J.A.
Abstract: Maize kernel deterioration caused by the action of insects has led to an urgent need to develop new control methods against the maize weevil, Sitophilus zeamais, one of the major pests found in silo bags during the storage of maize. Here, we evaluated the insecticidal efficiency of plasticized and unplasticized cotton matrices (deliveries), loaded with R-(+)-pulegone, (−)-carvone, 2-decanone and trans-2-hexenol against S. zeamais. R-(+)- pulegone was the only compound that produced weevil mortality. Plasticized delivery loaded with R-(+)-pulegone achieved a 90% mortality on the 12th day, with mortality values recorded of above 96% over the course of 30 days. R-(+)-pulegone from plasticized delivery was released more slowly compared to unplasticized delivery. Moreover, delivery loaded with R-(+)-pulegone did not show phytotoxicity in maize kernels. Hence, due to its effectiveness against the weevil and the lack of phytotoxic activity against maize kernels, plasticized delivery loaded with R-(+)-pulegone represents a promising material for S. zeamais control. However, large-scale studies are needed in order to evaluate its potential use in grain storage systems. Graphical abstract: Image 1 Highlights: Sitophilus zeamais affects maize kernels during storage in silo bags. Post-harvest grain deterioration raises the need for new methods to control insects. Plasticized delivery loaded with R-(+)-pulegone led to the highest mortality. Delivery loaded R-(+)-pulegone showed no phytotoxicity in grains. Plasticized cotton matrix with R-(+)-pulegone is optimum to apply in a grain storage system.